Microstructural Evaluation of Tool Steel Vanadis 6 after Sub-Zero Treatment at -140 °C without Tempering - Durica, Juraj; Jurci, Peter; Ptacinova, Jana (Manufacturing Technology Journal, 2018)
The microstructure, phase constitution and hardness of Cr-V ledeburitic tool steel Vanadis 6 subjected to sub-zero treatment at -140 °C and for different soaking times have been investigated. The microstructures have been characterized using the light microscopy, scanning electron microscopy and X-ray diffraction. The metallurgical aspects include the reduction of the retained austenite amount and increase in carbide count, as compared to conventionally heat treated material. The matrix is martensitic with certain amount of retained austenite, irrespectively to the time of sub-zero treatment. The amount of retained austenite has been significantly decreased from 20.2 vol. % to minimum 3.2 vol. % at 48 h soaking time. The microstructure of sub-zero treated steel contains eutectic, secondary and increased count of small globular carbides. The count of small globular carbides for conventionally heat treated samples was around 48 x 103 / mm2 and for sub-zero treated samples was increased more than four times with maximum 209 x 103 / mm2 at 24 h soaking time. These particles have size of up 500 nm but 100 nm in most cases. The hardness has been increased as compared to no sub-zero treated samples from 875 extpm 16 HV 10 up to 954.6 extpm 14 HV 10 at holding time 48 h.
Keywords: Sub-zero Treatment; Carbides; Martensite; Microstructure; Ledeburitic Steel